Design and implementation of a navigation system for autonomous mobile robots. (1st September 2010) - Sheu, Jang-Ping; Chang, Chia-Chi; Lo, Kai-Wen; Deng, Chi-Wen
In this paper, a navigation system for autonomous mobile robots is proposed. Our navigation system is a hybrid of behaviour-based and model-based navigation systems. In our system, a behaviour-based subsystem is in charge of low-level reactive actions, and a model-based subsystem is responsible for high-level planned actions. If there are obstacles in the way, the navigation system will use our obstacle avoidance algorithm to navigate around these obstacles and keep the robot moving towards the destination. On the basis of our experimental results, our navigation system can navigate the robot to the destination effectively.